Hydrogenation efficiency promotion through manipulating temperature-raising time for multi-crystalline silicon PERC solar cells. (March 2021) - Shao, Jianbo; Xi, Xi; Liu, Guilin; Li, Shaomin; Peng, Ruoying; Chen, Guoqing; Jiang, Yongfei; Sun, Jiangang
Abstract: Light injection and cooling conditions can induce some differences in the temperature-raising time of multi-crystalline silicon (mc-Si) solar cells. Through real-time tracking and monitoring of sample surface temperature, the temperature-raising steps for achieving the optimum efficiency improvement and degradation mitigation were optimized and modified. Then the corresponding hydrogenation treatments under a high-intensity infrared LEDs source were carried out based on improved steps. The results indicated that the optimal temperature-raising time should be manipulated at around 60 s and then followed by a 2-min hydrogenation treatment. Furthermore, the temperature-raising process should keep the temperature rising continuously without interruption or temperature drop. However, excessive thermal treatment time damaged the formation of defect precursors and extended the hydrogenation time. Moreover, the Fourier Transform Infrared spectrum curves illustrated that the peak intensity of the Si–H bonds treated at the 60-s temperature-raising time was more significant than that of other temperature-raising time treatments. Highlights: Manipulated temperature-raising steps bring more efficient hydrogenation. 60-s temperature-raising time and 2-min hydrogenation was optimum. Excessive temperature-raising time damaged the formation of defect precursors. 60-s temperature-raising time promoted the best peak intensity of Si–H bond.